Energy depletion and the economics of OPEC - Robinson, Colin (London : Henley Centre for Forecesting, 1975)
This paper, therefore, makes a valuable contribution in the field of forecasting on a subject of specific concern to business and governments world-wide.
aia 07/03/2019
Loans
Keywords: Oil and Gas; Energy